2014
DOI: 10.1021/la404055a
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Membrane-Binding Properties of N-Terminal and C-Terminal Regions of G Protein-Coupled Receptor Kinase 5 by Combined Optical Spectroscopies

Abstract: G protein-coupled receptor kinase 5 (GRK5) is thought to associate with membranes in part via N- and C-terminal segments that are typically disordered in available high-resolution crystal structures. Herein we investigate the interactions of these regions with model cell membrane using combined sum frequency generation (SFG) vibrational spectroscopy and attenuated total reflectance–Fourier transform infrared (ATR-FTIR) spectroscopy. It was found that both regions associate with POPC lipid bilayers but adopt di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…This allows for analysis of the specific interactions and structures at an interface or surface without the need to subtract for effects from bulk media or other sources of interference. SFG signal intensity is recorded as a function of IR wavenumber and yields information concerning peptide-lipid interactions, lipid bilayer structure and flip-flop, and peptide secondary structure and orientation 1922Figure 5Schematic diagram ( A ) of the experimental setup for sum frequency generation (SFG) spectroscopy analysis of lipid bilayer-peptide interactions; SFG O-H/N-H stretching signals collected from 22A peptide associated with egg sphingomyelin (eSM) at 20°C ( B ), 37°C ( C ), and 50°C ( D ); SFG amide range stretching signals collected from 22A peptide associated with eSM at 37°C ( E ) and 50°C ( F ); ppp refers to polarization combination of p-polarized SFG, p-polarized visible, p-polarized IR and ssp refers to s-polarized SFG, s-polarized visible, p-polarized IR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows for analysis of the specific interactions and structures at an interface or surface without the need to subtract for effects from bulk media or other sources of interference. SFG signal intensity is recorded as a function of IR wavenumber and yields information concerning peptide-lipid interactions, lipid bilayer structure and flip-flop, and peptide secondary structure and orientation 1922Figure 5Schematic diagram ( A ) of the experimental setup for sum frequency generation (SFG) spectroscopy analysis of lipid bilayer-peptide interactions; SFG O-H/N-H stretching signals collected from 22A peptide associated with egg sphingomyelin (eSM) at 20°C ( B ), 37°C ( C ), and 50°C ( D ); SFG amide range stretching signals collected from 22A peptide associated with eSM at 37°C ( E ) and 50°C ( F ); ppp refers to polarization combination of p-polarized SFG, p-polarized visible, p-polarized IR and ssp refers to s-polarized SFG, s-polarized visible, p-polarized IR.…”
Section: Resultsmentioning
confidence: 99%
“…Two broad peaks, centered at 3,200 and 3,400 cm −1 dominated the SFG spectrum for eSM and 22A at 20°C; they result from O-H stretching in ordered water structures near the lipid bilayer surface (Figures 5B and S6A). 22,30,31 The SFG spectrum for POPC at 20°C differed greatly, with a single peak at 3,300 cm −1 (Figure S6D). This peak represents the N-H stretch of ordered peptide secondary structure and suggests a strong interaction occurred between 22A peptide and the lipid bilayer 21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess which SNPs may affect GRK5 functionality and may be associated with AD risk, we performed a comprehensive screen of the coding region of the GRK5 gene for polymorphisms with minor allele frequency (MAF) > 0.01%. Finally, two non-synonymous polymorphisms in AD with potential functional impact were chosen to evaluate their possible effects on GRK5 function and their association with AD: cDNA nucleotide position 122 A/T changes glutamine (Gln) to leucine (Leu) at amino acid 41 (rs2230345) and nucleotide 840 G/A changes arginine (Arg) to histidine (His) at amino acid 304 (rs2230349) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…GRK5 is unique from GRK4 and 6 as it does not contain this palmitoylation site and rather depends on a positively charged lipid-binding elements in the form of an amphipathic helix for membrane association [14, 15]. Recently, it was found that GRK5 can associate with the plasma membrane via N-terminal residues 25–31 [16, 17]. …”
Section: Introduction To Grksmentioning
confidence: 99%